Extracellular Actin Is a Receptor for Mycoplasma hyopneumoniae - Raymond, Benjamin B. A.; Madhkoor, Ranya; Schleicher, Ina; Uphoff, Cord C.; Turnbull, Lynne; Whitchurch, Cynthia B.; Rohde, Manfred; Padula, Matthew P.; Djordjevic, Steven P. (Frontiers in Cellular and Infection Microbiology, 2018)
Mycoplasma hyopneumoniae, an agriculturally important porcine pathogen, disrupts the mucociliary escalator causing ciliostasis, loss of cilial function, and epithelial cell death within the porcine lung. Losses to swine production due to growth rate retardation and reduced feed conversion efficiency are severe, and antibiotics are used heavily to control mycoplasmal pneumonia. Notably, little is known about the repertoire of host receptors that M. hyopneumoniae targets to facilitate colonization. Here we show, for the first time, that actin exists extracellularly on porcine epithelial monolayers (PK-15) using surface biotinylation and 3D-Structured Illumination Microscopy (3D-SIM), and that M. hyopneumoniae binds to the extracellular β-actin exposed on the surface of these cells. Consistent with this hypothesis we show: (i) monoclonal antibodies that target β-actin significantly block the ability of M. hyopneumoniae to adhere and colonize PK-15 cells; (ii) microtiter plate binding assays show that M. hyopneumoniae cells bind to monomeric G-actin in a dose dependent manner; (iii) more than 100 M. hyopneumoniae proteins were recovered from affinity-chromatography experiments using immobilized actin as bait; and (iv) biotinylated monomeric actin binds directly to M. hyopneumoniae proteins in ligand blotting studies. Specifically, we show that the P97 cilium adhesin possesses at least two distinct actin-binding regions, and binds monomeric actin with nanomolar affinity. Taken together, these observations suggest that actin may be an important receptor for M. hyopneumoniae within the swine lung and will aid in the future development of intervention strategies against this devastating pathogen. Furthermore, our observations have wider implications for extracellular actin as an important bacterial receptor.